A New RP-HPLC Method for Simultaneous Determination of Amaroswerin, Amarogentin and Andrographolide in a Herbal Drug "Chirayata". (6th March 2022) - Sharma, Yash Pal; Bhardwaj, Chitralekha; Sharma, Reena; Thakur, Pancy; Sharma, Rohit
Abstract: Chirayata—the whole dried plant of Swertia chirayita— is an important traditional drug of Indian System of Medicines. A novel reverse-phase high performance liquid chromatography (RP-HPLC) method has been developed for the simultaneous determination and quantification of amaroswerin, amarogentin and andrographolide in a herbal drug "Chirayata, " which is oftenly adulterated/substituted with herbal drug Kalmegh. The developed method is in accordance with International Council for Harmonization guidelines and is simple, precise, accurate, rapid, reproducible and specific to determine amarogentin, amaroswerin and andrographolide. Reverse-phase column (Water's X-bridge C18, 5 μm, 4.6 mm × 250 mm) with high resolution for all marker compounds was used with binary gradient elution (methanol:water) with a flow rate of 1 mL/min and detection at 235 nm. The developed method showed good linearity ( R 2  > 0.999) in a relatively wider range of concentration 2.968–95.00 ppm for amarogentin, amaroswerin and 5.625–180 ppm for andrographolide. The method is important for quality control analysis of drug Chirayata.